The legacy of the Mastodon : the golden age of fossils in America - Thomson, Keith Stewart (Yale University Press, 2008)
"The uncovering in the mid-1700s of fossilized mastodon bones and teeth at Big Bone Lick, Kentucky, signaled the beginning of a great American adventure. The West was opening up, and unexplored lands beckoned. Unimagined paleontological treasures awaited discovery: strange horned mammals, birds with teeth, flying reptiles, gigantic fish, diminutive ancestors of horses and camels, and more than a hundred different kinds of dinosaurs. This exciting book tells the story of the grandest period of fossil discovery in American history, the years from 1750 to 1890." "The volume begins with Thomas Jefferson, whose keen interest in the American mastodon led him to champion the study of fossil vertebrates. The book continues with vivid descriptions of the actual work of prospecting for fossils - a pick in one hand, a rifle in the other - and enthralling portraits of Joseph Leidy, Ferdinand Hayden, Edward Cope, and Othniel Marsh, among other major figures in the development of the science of paleontology."--Jacket